Journal Influence in the Field of Management: An Analysis Using Salancik's Index in a Dependency Network - Johnson, Jonathan L.; Podsakoff, Philip M. (Academy of Management Journal, 1994)
We investigated changes in the influence of 40 publications relevant to the field of management between 1981 and 1986 and between 1986 and 1991 using Salancik's index of influence in a dependency network. Although the influence of many of the top journals stayed relatively stable over the decade, some notable changes occurred. The publications with the greatest increases in influence were the Academy of Management Review, the Academy of Management Journal, Strategic Management Journal, and Research in Organizational Behavior; Organizational Behavior and Human Decision Processes and the Psychological Bulletin had the greatest decreases. The results also provided general support for the validity of Salancik's index.